A New Species of the Genus Otites (Diptera, Ulidiidae) from Crete (Greece) - Kameneva, E.P. (Вестник зоологии, 2012)
Otites cretana Kameneva sp. n. from Crete (Psiloritis Ridge) is described. It superficially resembles Otites nebulosa (Latreille, 1812) and Dorycera persica Hennig, 1939 in the combination of very high gena and short antenna, but differs from all known Otitini by the thickened costal vein (in male), undulate vein R2+3, lacking ocellar setae and having 3 pairs of short scutellar setae. Status and generic limits of Otites and Dorycera are preliminary discussed.